Visionary Ventures: Cultivating Sustainable Entrepreneurship Across Cultures - Maspul, Kurniawan Arif (CV. Era Digital Nusantara, 2024)
The demand for sustainable business practices is higher than ever in today's world, which is characterised by environmental degradation, social inequity, and economic unpredictability. Sustainable entrepreneurship, which balances economic, social, and environmental aims, can lead to more ethical and resilient organizational operations. This study dives into the transformative journeys of Howard Schultz of Starbucks and Edward Tirtanata of Kopi Kenangan to show how businesses can succeed while solving global concerns. Schultz's vision of Starbucks as a